THE INFLUENCE OF WATCHING MOVIE WITH ENGLISH SUBTITLE ON VOCABULARY DEVELOPMENT IN SPEAKING SKILL OF NUSANTARA MARITIME ACADEMY BANJARMASIN - Rosiana, Elisa; Wardhana, Andri Ali (Pena Jangkar, 2023)
The current research sought to investigate the effect of watching a movie with English subtitles on the vocabulary development of Nusantara Maritime Academy Banjarmasin Cadets. A mixed method research methodology was used to achieve the goal of this study. A quasi-experimental design was used for the quantitative method, which was implemented using a quantitative research strategy. The qualitative method was employed in the research, with interviews conducted with participants in the experimental group. The researchers divided into two groups: control and experimental. In this study, only one group viewed the movie with English subtitles, while the other group watched the movie without subtitles. A pre-post test was performed, with the pre-test serving as a diagnostic test to see whether the cadets' vocabulary knowledge was similar, and the post test revealing whether the cadets' vocabulary knowledge had improved. Participants were thirty cadets studying for their O level exams. The research demonstrated that watching movies increases language knowledge. When the performances of the two groups were compared, it was discovered that the group that watched the films with captions outperformed the group that viewed the films without subtitles. In other words, it was discovered that intensively watching films with subtitles influenced ESL students' vocabulary knowledge. Furthermore, this study found that cadets in language classes in general, and vocabulary classes in particular, have good opinions toward watching films.